Plasma fibronectin in saliva of women with history of miscarriage(s) and periodontal disease - a pilot study - Farha Ariffin,; Salmah Kamin,; Jamiyah Hassan,; Haliza Hasan, (Universiti Kebangsaan Malaysia, 2013)
The objective of this study was to establish the association of plasma fibronectin in saliva of pregnant women with history of miscarriage(s). A total of 25 pregnant women with history of miscarriage(s) were recruited at the Antenatal Clinic of University Malaya Medical Centre (UMMC), Kuala Lumpur as the test group and 16 pregnant women without any history of miscarriage served as control. All the subjects fulfilled a set of inclusion and exclusion criteria. Periodontal examination was performed to determine subjects’ periodontal status. Saliva samples were collected and enzyme-linked immunosorbent assay (ELISA) was used to detect the plasma fibronectin in these samples. Mann-Whitney test was used to determine the significance of differences seen. The study showed a statistically significant higher median plasma fibronectin level in the saliva samples of the test group with a median level of 0.10 μg/mL compared with the control group with a mean value of 0.00 μg/mL (p-value =0.023). However, there was no significant difference in the level of plasma fibronectin in the saliva samples of pregnant women with chronic periodontitis compared with the group with healthy gingiva (p-value= 0.118). As a conclusion, there was a positive association between plasma fibronectin in saliva of women and history of miscarriages compared with the control group in this case study.